Experimental investigation of biogas production from feedlot cattle manure - Rosenberg, Logan; Kornelius, Gerrit (Journal of Energy in Southern Africa, 2017)
Biogas can be generated from biomass in an anaerobic digestion process and used to generate electricity and heat as an alternative energy source to fossil fuel-generated electricity. This study investigated biogas generation from cattle manure dried for periods up to 40 days. Manure samples were analysed for gas yield using the biochemical methane production test. The biogas volume produced by manure samples aged for periods up to 40 days after seeding with cattle rumen fluid was measured as a function of time until there was no further measurable gas production. The biogas was analysed for methane and carbon dioxide content using a gas chromatograph. The corresponding cumulative net biogas yield ranged from 154 to 369 Nml/g.VS respectively. The test results showed that an average of 240 Nml/g.VS of biogas can be produced from cattle manure that is less than 40 days old, with an average methane and carbon dioxide percentage of 63% and 31% respectively. Within 3 to 4 days the manure samples generated 80% of the final biogas volume. The drying process was found to occur at a constant rate per unit area, regardless of the manure thickness up to thickness of 200 mm. Biogas formation closely followed the Gompertz equation. There was no significant difference in the biogas production nor biogas production rate for cattle feedlot manure that was fresh up until aging to 40 days.